O agir do professor de inglês no youtube: considerações acerca dos saberes, gestos e práticas pedagógicas on-line. - Souza, Valdemir Melo de (2024)
Online teaching act has been the subject of countless studies, since online teaching appears to be an education trend of the future, encompassing digital technologies and access to cyberspace (Salles et al. 2023). The integration of YouTube with current digital technologies in English teaching has caused a lot of controversy due to the treatment that the media and communication channels have given to this social network. To the point of publications such as "Are youtubers changing the way we educate?" This has attracted the attention of several researchers (Mutz; Gomes, 2022), since the work of the teacher requires a certain complexity and online pedagogical practices demand even greater depth. This leads us to question the use of the YouTube social network and its effectiveness as an educational environment. In the context of contemporary education, it is important to highlight what teachers who have used this technology have to say, especially the aspects that add to possible innovations in English teaching. In this sense, the study of teaching action helps us to understand the multiple dimensions that involve the work of teachers, their practices, knowledge and activities carried out in different teaching contexts. With the intention of investigating action in an online context, the general aim of this thesis is to analyze the pedagogical practice of English language teachers on YouTube, considering the teaching knowledge and didactic gestures mobilized by these teachers/workers in order to discern to what extent the use of this social network promotes innovative practices in English classes. From a methodological point of view, the research is characterized as qualitative and netnographic, since its participants make up the groups and virtual communities that have emerged with the internet (Kozinets, 2014). The theoretical contributions come from Sociodiscursive Interactionism (SID), Bronckart 2006; 2008), Machado (2004), and from the Work Sciences (Ergonomics and Activity Clinic), which offers the procedures of instruction to the professor (Clot, 2007) as an instrument for analyzing teaching action. The research results revealed five conceptions of teachers in English classes, as well as the teaching knowledge and specific gestures of the teachers most mobilized in the YouTube virtual environment. Therefore, given the evidence found, data analysis shows that online pedagogical practice on YouTube is driven by knowledge arising from the teacher's experiences from the school floor, with oral exposition being the main gesture that permeates activities on this platform, since the structure and functioning of this social network brings restrictions on the teacher's actions, which interferes with innovations in English classes.